Retinal and choroidal efficacy of switching treatment to faricimab in recalcitrant neovascular age related macular degeneration - Franziska Eckardt; Anna Lorger; Michael Hafner; Julian Elias Klaas; Benedikt Schworm; Thomas Christian Kreutzer; Siegfried Georg Priglinger; Jakob Siedlecki (Scientific Reports, 2024)
Abstract Aim of this study was to evaluate the efficacy of switching treatment to faricimab in neovascular age-related macular degeneration (nAMD) from other anti-VEGF agents. Fifty-eight eyes of fifty-one patients with nAMD and a full upload series of four faricimab injections were included. Demographic data, multimodal imaging and treatment parameters were recorded. The primary outcome measures were changes in central subfield thickness (CST) and subfoveal choroidal thickness (SFCT). A subgroup analysis was performed for eyes with prior ranibizumab (R) or aflibercept (A) treatment. Mean injection intervals before and after switching were comparable (33.8 ± 11.2 vs. 29.3 ± 2.6 days; p = 0.08). Mean CST of 361.4 ± 108.1 µm prior to switching decreased significantly to 318.3 ± 97.7 µm (p < 0.01) after the third faricimab injection, regardless of prior anti-VEGF treatment (p < 0.01). Although SFCT slightly improved for the whole cohort from 165.8 ± 76.8 µm to 161.0 ± 82,8 µm (p = 0.029), subgroup analysis did not confirm this positive effect (subgroup R: p = 0.604; subgroup A: p = 0.306). In patients with a suboptimal response to aflibercept or ranibizumab in nAMD, farcimab can improve CST and slightly improve or maintain SFCT. Further prospective randomized trials are warranted.